Electrical percolation, morphological and dispersion properties of MWCNT/PMMA nanocomposites - Coelho,Paulo Henrique da Silva Leite (2014)
Nanocomposites of poly (methyl methacrylate) (PMMA) and carbon nanotubes have a high potential for applications where conductivity and low specific weight are required. This piece of work concerns investigations of the level of dispersion and morphology on the electrical properties of in situ polymerized nanocomposites in different concentrations of multi-walled carbon nanotubes (MWCNT) in a PMMA matrix. The electrical conductivity was measured by the four point probe. The morphology and dispersion was analyzed by Transmission Electron Microscopy (TEM) and Small Angle X-ray Scattering (SAXS). The correlation between electrical conductivity and the MWCNT amount, presented a typical percolation behavior, whose electrical percolation threshold determined by power law relationship was 0.2 vol. (%) The exponent t from the percolation power law indicated the formation of a 3D network of randomly arranged MWCNT. SAXS detected that the structures are intermediate to disks or spheres indicating fractal geometry for the MWCNT aggregates instead of isolated rods. HR-TEM images allowed us to observe the MWCNT individually dispersed into the matrix, revealing their distribution without preferential space orientation and absence of significant damage to the walls. The combined results of SAXS and HR-TEM suggest that MWCNT into the polymeric matrix might present interconnected aggregates and some dispersed single structures.